'Discuss it with your legal guardian': Challenges in practising care for young unaccompanied refugee minors. Issue 3 (26th November 2020) - Omland, Guro Brokke; Andenas, Agnes; Sveaass, Nora
Abstract: How is care arranged for unaccompanied refugee minors at residential care institutions, and what kind of conditions do these arrangements constitute for young persons' well‐being and development? Informed by developmental perspectives that consider young people's development through participation across contexts in everyday life and by research into how parents in 'ordinary' families organize care, we developed a study based on interviews with 15 unaccompanied refugee minors and their professional caregivers at residential care institutions. The interviews were analysed systematically by exploring how care is arranged between professionals and its implications in the young persons' lives. The results elucidate how responsibility for following up and making sense of central issues in the lives of the minors was allocated to professionals outside the daily care rather than being part of the primary caregivers' contact with the minors. This practice contrasts with what young persons in 'ordinary families' in Norway enjoy, where coordination across contexts and keeping an overview of the total care are considered the responsibility of parents. The article focuses on the outsourcing of what we call refugee‐related legal issues in the minors' everyday lives, to the legal guardians, which appeared to be a barrier to being understood and supported.